Recent Advancement in Anticancer Activity of Clinacanthus nutans (Burm. f.) Lindau. (27th May 2021) - Lin, Chung-Ming; Chen, Hsin-Han; Lung, Chi-Wen; Chen, Hui-Jye
Abstract : Clinacanthus nutans is a traditional medicinal herb that is applied for the therapy of snake bites, skin infection, herpes infection, burns, scalds, dysentery, and diabetes. Clinacanthus nutans is also used to treat several cancers, including breast, cervical, colon, gastric, head and neck, liver, lung, pancreatic, and skin cancers, as well as lymphoma and leukemia; however, the underlying mechanisms of its anticancer activity remained undetermined. We searched PubMed and Google with key words " Clinacanthus nutans and cancer" and collected recent papers of Clinacanthus nutans with anticancer activity. We focused on the preparation, effects, and action mechanisms of Clinacanthus nutans extracts on various types of cancers. We hope that this mini review can help update our knowledge about active components, effects, and molecular mechanisms of extracts from this promising herb Clinacanthus nutans for ongoing studies and speed up its clinical application in the future.